Pengembangan Media Pembelajaran Budaya Minangkabau Menggunakan Adobe Flash untuk Meningkatkan Minat dan Antusiasme Siswa - Priyanto, Dimas Putra; Annas, Firdaus; Al Hafidz, Muhammad Husein (Journal of Educational Management and Strategy, 2024)
This research aims to create interactive learning media using Adobe Flash so that students are more interested and understand the lessons of Minangkabau Culture. The background of this research is the low interest of students in learning the lesson, which is caused by traditional teaching methods that only use lectures and the lack of interesting learning tools. This research uses the Research and Development (R&D) method with the 4D development model, which consists of the Determine, Design, Develop, and Deploy stages. At the Defining stage, a needs analysis was conducted to find problems and learning objectives. The Designing stage produces an interactive learning tool design that incorporates visual elements typical of Minangkabau Culture, such as songket patterns and gadang houses. At the Developing stage, this learning tool is created with interactive features such as quizzes and educational games, and tested by media and material experts. The Deploy stage includes the dissemination of learning tools through training for teachers, digital distribution, and educational seminars. The results of the study show that the learning media made are valid and can be used, and can increase students' interest in learning. This media also helps teachers in teaching the material in a more creative and interactive way. Thus, this research is expected to be a solution to improve the quality of learning Minangkabau Culture.